2021
DOI: 10.1007/s11605-020-04561-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Pre-operative Exercise and the Response to Prehabilitation in Oesophageal Cancer Patients

Abstract: Background Prehabilitation is thought to reduce post-operative respiratory complications by optimising fitness before surgery. This prospective, single-centre study aimed to establish the effect of pre-operative exercise on cardiorespiratory fitness in oesophageal cancer patients and characterise the effect of adherence and weekly physical activity on response to prehabilitation. Methods Patients received a personalised, home-based pre-operative exercise programme and self-reported their adherence each week. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…A previous study of patients participating in the PREPARE for Surgery programme found that the incidence of post-operative pneumonia was significantly related to the amount of exercise completed in the pre-operative period. 32 The mechanism by which prehabilitation reduces post-operative pneumonia is likely to be multi-factorial. Prehabilitation has been shown to improve cardio-respiratory fitness in a range of patient populations, including oesophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study of patients participating in the PREPARE for Surgery programme found that the incidence of post-operative pneumonia was significantly related to the amount of exercise completed in the pre-operative period. 32 The mechanism by which prehabilitation reduces post-operative pneumonia is likely to be multi-factorial. Prehabilitation has been shown to improve cardio-respiratory fitness in a range of patient populations, including oesophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Details of our exercise programme have previously been published 32 and are summarised below. A personalised, home-based exercise programme was prescribed by an exercise therapist.…”
Section: Exercise Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Outcome measures varied widely between the studies. Exercise capacity was measured using a cardiopulmonary exercise test (CPET) [10,27e30], 6-min walk test (6MWT) [9,30e38], incremental shuttle walk test (ISWT) [39], chester step test [40] steep ramp test [41] or 2-min walk test [42]. Muscle strength was measured in terms of hand grip strength (HGS) [9,30,31,33,35,41e46], knee extensor muscle strength [9,30,32,33,38,41], chair stand test [42,47], heel raising test [47], maximal inspiratory pressure (MIP) [30,42] or maximal expiratory pressure (MEP) [30].…”
Section: Resultsmentioning
confidence: 99%
“…In several studies an exercise intervention was implemented in the pre-or postoperative phase as part of the usual care treatment (see Supplementary Table A.1). Four studies described a preoperative exercise intervention with the duration of at least one week [30,33,37,40]. In two studies patients were only advised to be physically active [41,48], and in two studies patients only received breathing exercises [34,38].…”
Section: Resultsmentioning
confidence: 99%